Extraction of Biocompatible Collagen From Blue Shark Skins Through the Conventional Extraction Process Intensification Using Natural Deep Eutectic Solvents - Batista, Miguel P.; Fernández, Naiara; Gaspar, Frédéric B.; Bronze, Maria do Rosário; Duarte, Ana Rita C. (Frontiers in Chemistry, 2022)
The disposal of large amounts of skin waste resulting from the blue shark fishing industry presents several industrial and environmental waste management concerns. In addition, these marine subproducts are interesting sources of collagen, a fibrous protein that shows high social and economic interest in a broad range of biomedical, pharmaceutical, and cosmetic applications. However, blue shark wasted skins are a poorly explored matrix for this purpose, and conventional collagen recovery methodologies involve several pre-treatment steps, long extraction times and low temperatures. This work presents a new green and sustainable collagen extraction approach using a natural deep eutectic solvent composed of citric acid:xylitol:water at a 1:1:10 molar ratio, and the chemical characterization of the extracted collagen by SDS-PAGE, thermogravimetric analysis, Fourier transformed infrared spectroscopy and circular dichroism. The extracted material was a pure type I collagen, and the novel NADES approach presented an extraction yield 2.5 times higher than the conventional one, without pre-treatment of raw material and reducing the procedure time from 96 h to 1 h. Furthermore, the in vitro cytotoxicity evaluation, performed with mouse fibroblasts NCTC clone 929 cells, has proven the biocompatibility of the extracted material. Overall, the obtained results demonstrate a simple, quick, cheap and environmentally sustainable process to obtain marine collagen with promising properties for biomedical and cosmetic applications.